The collected short plays of Thornton Wilder. - Wilder, Thornton, 1897-1975 (Theatre Communications Group, 1997)
Volume Two of the collected short plays by one of the greatest American playwrights of the 20th century. Now available once more here is the author's long out-of-print first collection of one-acts, The Angel that troubled Tthe waters, along with three occasional plays, two of them previously unpublished, and Wilder's full-length play, The Alcestiad, or a Life in the sun.